The emerging hydrogen economy and its impact on LNG - Omran Al-Kuwari; Max Schönfisch (Institute of Energy Economics at the University of Cologne (EWI), 2021)
Hydrogen is gaining prominence as a critical tool for countries to meet decarbonisation targets. The main production pathways are based on natural gas or renewable electricity. LNG represents an increasingly important component of the global natural gas market. This paper examines synergies and linkages between the hydrogen and LNG values chains and quantifies the impact of increased low-carbon hydrogen production on global LNG flows. The analysis is conducted through interviews with LNG industry stakeholders, a review of secondary literature and a scenario-based assessment of the potential development of global low-carbon hydrogen production and LNG trade until 2050 using a novel, integrated natural gas and hydrogen market model. The model-based analysis shows that low-carbon hydrogen production could become a significant user of natural gas and thus stabilise global LNG demand. Furthermore, commercial and operational synergies could assist the LNG industry in developing a value chain around natural gas-based low-carbon hydrogen.
Keywords: Q40; Q42; Q49; 330; Hydrogen; LNG; natural gas